Modern approaches to the pre-induction cervical ripening of mifepristone - О. В. Кравченко (Publishing House TRILIST, 2018)
The article deals modern approaches used of mifepristone in order to prepare the cervix for delivery. The results of a study of 222 patients in the gestation period of 37-42 gestation weeks which given orally administered 200 mg of mifepristone at intervals of 24 hours for 2 days are presented. The criteria for inclusion in the study: the age of the pregnant 18-40 years, the independent onset of pregnancy, singleton pregnancy, head presentation, the presence of intact fetal membranes; absence of contraindications to the use of mifepristone. Before the preparation of the cervix for delivery, an assessment was made of the condition of the mother and fetus, which included clinical examinations and cardiotocography before pre-induction, as well as cardiotocography control in dynamics. Before receiving mifepristone, the cervix was evaluated as "immature" in 60.3% of pregnant women, in 39.6% of patients it was "not mature enough". After taking the first pill of mifepristone, 44.6% of pregnant women against the background of the already "mature" cervix of the uterus developed an independent labor activity. Development of labor activity occurred in 32.3% of pregnant women within 12 hours after taking the drug, in 26.3% in the interval from 12 to 24 hours, in 46.5% - later than in 24 hours. The remaining 55.4% of patients needed the appointment of a second tablet of mifepristone, after which the cervix became "mature" in 69.1% of patients, of which 90.6% of women developed independent labor. As a result of the research it was proved that the use of mifepristone is a highly effective method of preparing the body for pregnant women to delivery, the efficiency of labor is 79.3%. Pre-induction of mifepristone for more than 41 weeks is less effective in relation to cervical maturation and the development of regular birth activity, which makes it possible to characterize the gestational period of 40-41 weeks, as optimal for the cervical effacement and the induction of labor. The use of mifepristone does not lead to a negative effect of the fetal condition.